Microstructure, mechanical property, corrosion behavior, and in vitro biocompatibility of Zr–Mo alloys1. Issue 2 (10th November 2012) - Zhou, F. Y.; Wang, B. L.; Qiu, K. J.; Li, L.; Lin, J. P.; Li, H. F.; Zheng, Y. F.
Abstract: In this study, the microstructure, mechanical properties, corrosion behaviors, and in vitro biocompatibility of Zr–Mo alloys as a function of Mo content after solution treatment were systemically investigated to assess their potential use in biomedical application. The experimental results indicated that Zr–1Mo alloy mainly consisted of an acicular structure of α′ phase, while ω phase formed in Zr–3Mo alloy. In Zr–5Mo alloy, retained β phase and a small amount of precipitated α phase were observed. Only the retained β phase was obtained in Zr–10Mo alloy. Zr–1Mo alloy exhibited the greatest hardness, bending strength, and modulus among all experimental Zr–Mo alloys, while β phase Zr–10Mo alloy had a low modulus. The results of electrochemical corrosion indicated that adding Mo into Zr improved its corrosion resistance which resulted in increasing the thermodynamic stability and passivity of zirconium. The cytotoxicity test suggested that the extracts of the studied Zr–Mo alloys produced no significant deleterious effect to fibroblast cells (L‐929) and osteoblast cells (MG 63), indicating an excellent in vitro biocompatibility. Based on these facts, certain Zr–Mo alloys potentially suitable for different biomedical applications were proposed. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.